2017
DOI: 10.18052/www.scipress.com/ilshs.75.22
|View full text |Cite
|
Sign up to set email alerts
|

A Double Label: Learning Disabilities and Emotional Problems among Gifted Children

Abstract: Abstract. Many gifted children are "double labeled", namely in addition of being gifted they are also learning disabled and/or suffer from emotional, social or behavioral problems. This article will present the difficulties gifted children with a double label have to deal with, especially the difficulties in the educational system. Because of the double label the educational team faces a double challenge, in most cases without being equipped with the required knowledge or the support they need. This article wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 37 publications
1
5
0
Order By: Relevance
“…In the international literature, interest in 2e students and their educational needs is increasing (Assouline, Foley Nicpon, & Huber, 2006;David, 2017;Wang & Neihart, 2015;Webb et al, 2016). To date, what is known from this literature is that 2e students are a special and distinctive population who simultaneously have a high cognitive abilitye.g., a logical-mathematical intelligence (Gardner, 1999) associated with an academic (e.g., mathematical) giftedness and a weakness associated with a disability such as SLD (gifted/SLD), ADHD (gifted/ADHD), ASD (gifted/ASD) or ED (gifted/ED).…”
Section: Twice-exceptionality and The Problems Of "Misdiagnosis" And ...mentioning
confidence: 99%
“…In the international literature, interest in 2e students and their educational needs is increasing (Assouline, Foley Nicpon, & Huber, 2006;David, 2017;Wang & Neihart, 2015;Webb et al, 2016). To date, what is known from this literature is that 2e students are a special and distinctive population who simultaneously have a high cognitive abilitye.g., a logical-mathematical intelligence (Gardner, 1999) associated with an academic (e.g., mathematical) giftedness and a weakness associated with a disability such as SLD (gifted/SLD), ADHD (gifted/ADHD), ASD (gifted/ASD) or ED (gifted/ED).…”
Section: Twice-exceptionality and The Problems Of "Misdiagnosis" And ...mentioning
confidence: 99%
“…], Eating problems: mainly anorexia or bulimia. The moderate version is distorted self-image, striking as early as at age 6 [with girls affected at much younger age than boys -not only at a much higher frequency]; Discipline problems: the child misbehaves at school, at home or in both places; School refusal: the child refusal to go to school [or to the kindergarten] Behavioral problems, such as rage attacks, acting out, Self-harm or self-injury: scratching, biting, cutting, and the like, Suicidal threats or even suicidal attempts (David, 2016b).…”
Section: The Main Problems Motivating Parents To Seek Counselingmentioning
confidence: 99%
“…Schools all over the world have recently suffered from student problems that seem clearly obvious, whether academic, behavioural, social or emotional, the school administration called for urgently solving them. These problems have become a major barrier in achieving the school's ultimate goal, which is to provide school ‫لتنمية‬ ‫وا‬ ‫ية‬ ‫لرتبو‬ ‫ا‬ ‫للبحوث‬ ‫لقومي‬ ‫ا‬ ‫املركز‬ ‫ـ‬ 91 ‫ـ‬ environment meet the needs of students (Athanasoula & Lazaridou, 2008).Many researchers (e.g., Tannenbaum, 2000;Rayneri, Gerber & Wiley, 2003;David, 2017) indicated that students' problems in preparatory school can show up as poor academic performance, lack of motivation for school, loss interesting in schoolwork, and poor relationships with peers or teachers.Many studies focused on academic outcomes and concern academic problems such as low attendance, decreasing academic achievement, and dropping out of school (Benner & Graham, 2009). There might be several reasons behind these academic problems.Students' connection with the school is one of the main reasons, and studies showed that developing a good connection with the school increases academic success and positive social behaviours.…”
mentioning
confidence: 99%
“…Many researchers (e.g., Tannenbaum, 2000;Rayneri, Gerber & Wiley, 2003;David, 2017) indicated that students' problems in preparatory school can show up as poor academic performance, lack of motivation for school, loss interesting in schoolwork, and poor relationships with peers or teachers.…”
mentioning
confidence: 99%
See 1 more Smart Citation